Validity of the SenseWear armband to assess energy expenditure during intermittent exercise and recovery in rugby union players - Zanetti, S.; Pumpa, K. L.; Wheeler, K. W.; Pyne, D. B. (The Journal of Strength and Conditioning Research, 2014)
Portable wearable devices that assess energy expenditure during intermittent exercise and recovery would be useful in team sports. Fourteen state-level male rugby union players (mean ± SD: age, 22 ± 4 years; body mass, 88.8 ± 11.2 kg; height, 1.81 ± 0.07 m, body fat, 18 ± 6% ) participated in this study. Energy expenditure was measured by the SenseWear Armband (SWA) and validated against indirect calorimetry as the criterion measure during a 42-minute rugby-specific intermittent exercise test and an immediate postexercise 10-minute recovery period. Energy expenditure measurements from indirect calorimetry and the SWA were only moderately correlated during both the exercise test (r = 0.55, ±0.34; mean, ±90% confidence limits) and recovery period (r = 0.58, ±0.33). The SWA estimate of energy expenditure during exercise was unclear, with a mean bias of -1.9% (±5.3%), and during recovery energy expenditure was overestimated, with a mean bias of 17% (±12%) at the mean estimated energy expenditure. Typical error of SWA energy expenditure estimates expressed as a coefficient of variation (±90% confidence interval) was 10% (8-16%) during exercise and 19% (14-30%) during recovery. The SWA did not provide a valid measure of energy expenditure during rugby-specific intermittent exercise or 10-minute postexercise recovery. Further improvements are required in the performance of the SWA before it can be used routinely in intermittent sports and provide worthwhile information in relation to workloads of athletes for sport scientists and coaches.